Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Dave Watkins standing by Model T Ford; Driver Homer Shoemaker; children Margaret Robinson Annie, Madeline, Gilletta, Geneva Robertson and Pauline Gibson Shoemaker